Stigmatization and discrimination in patients with HIV/AIDS: A systematic literature review - Muhammad Amirul Mukminin; Nurfika Asmaningrum; Dicky Endrian Kurniawan (Journal of Holistic Nursing Science, 2023)
Patients with AIDS commonly feel negative impressions of themselves; vice-versa, other people will lead to negative stigma. In addition, stigma has a significant impact, affecting themselves and how people treat them. This study aims to identify the impact and determinants of stigmatization and discrimination toward people with HIV/AIDS. A systematic review was used as the research design guided by the PRISMA framework. The researchers sought the other studies' results through several databases, including PubMed, ProQuest, ScienceDirect, Google Scholar, and Clinical Key for Nursing. Nineteen articles were reviewed, which highlighted that stigmatization and discrimination could be physical, verbal, and social. Our findings showed that stigmatization and discrimination occur in various forms because of accompanying factors. Several risk factors need to be reviewed as the starting point for developing measures to address stigmatization and discrimination. Keywords: Mental health; nursing care; HIV; AIDS; Stigma; Discrimination